Computed tomography evaluation of rotary systems on the root canal transportation and centering ability - André PAGLIOSA; Manoel Damião SOUSA-NETO; Marco Aurélio VERSIANI; Walter RAUCCI-NETO; Yara Teresinha Corrêa SILVA-SOUSA; Edson ALFREDO (Sociedade Brasileira de Pesquisa Odontológica, 2015)
Abstract : The endodontic preparation of curved and narrow root canals is challenging, with a tendency for the prepared canal to deviate away from its natural axis. The aim of this study was to evaluate, by cone-beam computed tomography, the transportation and centering ability of curved mesiobuccal canals in maxillary molars after biomechanical preparation with different nickel-titanium (NiTi) rotary systems. Forty teeth with angles of curvature ranging from 20° to 40° and radii between 5.0 mm and 10.0 mm were selected and assigned into four groups (n = 10), according to the biomechanical preparative system used: Hero 642 (HR), Liberator (LB), ProTaper (PT), and Twisted File (TF). The specimens were inserted into an acrylic device and scanned with computed tomography prior to, and following, instrumentation at 3, 6 and 9 mm from the root apex. The canal degree of transportation and centering ability were calculated and analyzed using one-way ANOVA and Tukey's tests (α = 0.05). The results demonstrated no significant difference (p > 0.05) in shaping ability among the rotary systems. The mean canal transportation was: -0.049 ± 0.083 mm (HR); -0.004 ± 0.044 mm (LB); -0.003 ± 0.064 mm (PT); -0.021 ± 0.064 mm (TF). The mean canal centering ability was: -0.093 ± 0.147 mm (HR); -0.001 ± 0.100 mm (LB); -0.002 ± 0.134 mm (PT); -0.033 ± 0.133 mm (TF). Also, there was no significant difference among the root segments (p > 0.05). It was concluded that the Hero 642, Liberator, ProTaper, and Twisted File rotary systems could be safely used in curved canal instrumentation, resulting in satisfactory preservation of the original canal shape.